Louis-Sébastien Mercier and the power of books in the utopia of the Enlightenment: the role of the library in L'An 2440 - Morriello, Rossana (Bibliothecae.it, 2025)
This article examines the role of books and libraries during the Age of Enlightenment through the lens of Louis-Sébastien Mercier’s work, a prominent figure of French Enlightenment thought. Central to the article is his novel L’An 2440, rêve s’il en fut jamais (1770–1771), which may be considered both a manifesto of Enlightenment ideals and an early example of science fiction and uchronia. A pivotal chapter devoted to the King’s Library serves as the culmination of Mercier’s broader reflection on the significance of books and print culture as vehicles for the dissemination of progressive ideas. The first part of the study provides a historical and literary contextualization of the concept of uchronia, situating Mercier’s novel within broader traditions of utopian and bibliographic studies. The concluding section addresses the contemporary relevance of utopian thought and considers the library as a symbolic space of resistance, imagination, and engagement in times of social and political complexity.